El Toro 1936-03 (March 1936) - San Jose State College:::Creator::::::::::::; Rector, Helen; Starr, Marion; Brayton, Frank:::Editor::::::::::::
Founded in 1935 by Jordan Kellogg, El Toro was a college humor magazine featuring short jokes, cartoons, and articles of a satirical or humorous nature.